Immunocytochemistry as An Adjunctive Diagnostic Tool in Cytology - Bhardwaj, Swati; Ahluwalia, Charanjeet; Singh, Mukul; Kolte, Sachin; Madan, Neha; Arora, Rashmi; Dhawan, Indrani (Annals of Pathology and Laboratory Medicine, 2019)
Background: Cytology is rapidly progressing from a primary screening investigation to a definitive diagnostic modality in increasing number of cases. This has been made possible by the use of ancillary tests such as immunochemistry, and molecular techniques. Over the years, the use of immunochemistry has evolved from being just an adjunct to diagnosis, to determining primary site of malignancy and exact typing of malignancies. This study was conducted to find out the impact of immunochemistry performed on cell blocks and smears of varied cytology material including FNAC material and fluids. Methods: It was a retrospective study. All cytology cases including FNAC material and fluids on which immunochemistry had been performed were retrieved from records. Immunochemistry was performed manually on cold acetone fixed smears, and cell-block preparations. Result: A total of 50 cases were evaluated from past two years, including 10 cases of fluids, and 40 cases of FNAC material. Staining was done on cell blocks in 44 cases, and on smears in 6 cases. In 15 cases, immunochemistry was performed to find out the site of primary malignancy, of which in 11 cases, it was positively contributory in giving a list of possible primaries and in 4 cases, single definitive diagnosis was provided. In 27 cases, it helped in typing of malignancies, and providing additional information. It was non-contributory in 8 cases. Conclusion: Immunochemistry, on smears as well as cell blocks is a useful adjunctive tool in cytology, therefore, it is advised to perform immunochemistry wherever possible.